2004
DOI: 10.1097/01.mnm.0000130243.06821.90
|View full text |Cite
|
Sign up to set email alerts
|

99mTc glucarate high-resolution imaging of drug sensitive and drug resistant human breast cancer xenografts in SCID mice

Abstract: Background and aim-Previous studies have showed that 99m Tc labelled glucarate (GLA) might be an agent for non-invasive detection of breast tumours. In xenografted BT20 breast tumours, GLA was found to have higher uptake than 99m Tc sestamibi (MIBI). It is unclear whether GLA can localize in all cell line breast cancer xenografts, as well as breast tumours with multidrug resistance (MDR). The present study aimed to investigate the properties of GLA in detecting drug sensitive and drug resistant MCF7 breast can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…T ODAY, small animal Single Photon Emission Computed Tomography (SPECT) pinhole imaging [1;2] can yield excellent image resolutions [3][4][5] down to the sub-half-mm scale [6;7]. At present these ultra-high resolutions are obtained using traditional gamma cameras, by employing the principle of pinhole magnification.…”
Section: Introductionmentioning
confidence: 99%
“…T ODAY, small animal Single Photon Emission Computed Tomography (SPECT) pinhole imaging [1;2] can yield excellent image resolutions [3][4][5] down to the sub-half-mm scale [6;7]. At present these ultra-high resolutions are obtained using traditional gamma cameras, by employing the principle of pinhole magnification.…”
Section: Introductionmentioning
confidence: 99%
“…Glucarate (GLA), a normal metabolite of D-glucuronic acid, is a small, six-carbon dicarboxylic acid compound that is excreted in urine, and has long been used as a stabilizer for calcium gluconate injections. GLA can be labeled by sodium pertechnetate Nuclear Medicine and Biology 42 (2015) 608-613 (Na[ 99m TcO 4 ]), thus forming 99m Tc-GLA [11,15]. Experimental studies suggest that 99m Tc-GLA tends to be concentrated in the heart and brain with local ischemia and early necrosis [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…As a promising 99m Tc-labeled analog, 99m Tc-glucarate ( 99m Tc-GLA) has been investigated in various tumor imaging studies [10][11][12][13][14][15], and has been found to exhibit different pharmacology and pharmacokinetics compared to those of 18 F-FDG. Glucarate (GLA), a normal metabolite of D-glucuronic acid, is a small, six-carbon dicarboxylic acid compound that is excreted in urine, and has long been used as a stabilizer for calcium gluconate injections.…”
Section: Introductionmentioning
confidence: 99%
“…Imaging small-animal models of cancer can illustrate the interaction of the tumor with its microenvironment, but further work is required to generate a sufficient library of imaging agents, because the translation of in vitro assays into SPECT agents is challenging (74). In the case of chemotherapy planning and evaluation for multidrug resistance, small-animal SPECT/CT has characterized several radiopharmaceuticals used to monitor the expression or activity of the transmembrane p-glycoprotein pump, including 99m Tc tetrofosmin, 99m Tc-sestamibi (80), and a Schiff base 67 Ga(III) complex (81), and compared their efflux with that of radiopharmaceuticals resistant to washout by p-glycoprotein-expressing tumors (82). These types of studies require rapid dynamic small-animal SPECT, similar to the need described earlier.…”
Section: Cardiovascular Applicationsmentioning
confidence: 99%